1974
DOI: 10.1079/bjn19740067
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional nutritional and anthropometric study, with an interval of 7 years, on 611 young adolescent schoolchildren

Abstract: I. A study of the food intake, during a period of 7 consecutive days, was made on 192 boys and girls, aged 14 years, attending Glasgow schools in 1964. A similar study was done in 1971 on 419 boys and girls of the same age. The children came from all the various socio-economic backgrounds and were subdivided into four social groups.2. The heights and body-weights of the groups studied in 1964 and 1971 were similar but the percentage contribution of fat to the body-weight had increased in the boys. (4) showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
28
2
1

Year Published

1975
1975
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(34 citation statements)
references
References 9 publications
3
28
2
1
Order By: Relevance
“…19 The inverse association between adiposity and energy intake was not anticipated and had not been observed in previous cross-sectional analyses of the NGHS baseline data. 29 However, inverse associations have been observed in other cross-sectional studies in adults 30,31 and in children 32 and could be a result of reporting bias, where heavier individuals tend to underreport their food intake. 33 In contrast, it could be attributable to behavior change, where heavier individuals wishing to lose weight attempt to reduce their energy intake.…”
Section: Discussionmentioning
confidence: 65%
“…19 The inverse association between adiposity and energy intake was not anticipated and had not been observed in previous cross-sectional analyses of the NGHS baseline data. 29 However, inverse associations have been observed in other cross-sectional studies in adults 30,31 and in children 32 and could be a result of reporting bias, where heavier individuals tend to underreport their food intake. 33 In contrast, it could be attributable to behavior change, where heavier individuals wishing to lose weight attempt to reduce their energy intake.…”
Section: Discussionmentioning
confidence: 65%
“…The trend of increased body fatness and decreased energy intake recorded in several studies 2,3,38 suggest a trend of decrease in physical activity. In a previous study, conducted in 10 y old children examined in 1978, we observed that these children consumed more energy than the 10 y old children of the present study (2326 in 1978 and 2102 kcal in 1995) and had a weaker BMI (16.5 and 17 kg/m 2 respectively).…”
Section: Discussionmentioning
confidence: 99%
“…However, this was not as great as noted by previous studies (4)(5)(6) , and many significant differences between the lunch types existed at the end of the day.…”
mentioning
confidence: 50%